Assessment of Sleep Disorders in Adolescents in Wartime - Kabantseva Anastasiia; Panchenko Oleg; Serdyuk Iryna; Guryanov Vitaly (Insight: the psychological dimensions of society, 2025)
Preventing the negative consequences of hostilities and addressing sleep problems in adolescents are critical issues in times of danger. The purpose of the study is to identify the key factors associated with sleep disorders in adolescents in wartime. Methods. The total sample of the study consisted of 489 adolescents aged 10 to 15 years who were exposed to war in Ukraine. The methods used included observation, interviews, questionnaires, and testing. The psychodiagnostic battery included the following instruments: the “School-Age Child Integration Questionnaire” and the “Children’s Neurosis Questionnaire”. Results. Analysis of the scores using the “Children’s Neurosis Questionnaire” revealed a high level of sleep disturbance in 85 adolescents (17.4%) and a moderate level in 99 adolescents (20.2%). Adolescents with severe disorders require medical and psychological assistance, while those with moderate disorders are considered at risk; therefore, it is advisable to conduct psychoprophylactic interventions to prevent the development of psychosomatic and mental disorders. The results of univariate and multivariate analyses confirmed the hypothesis that the main factors increasing the risk of sleep disorders are being female, living in a combat zone, fear of war, feeling uncomfortable within the family, lack of a favorable family relationship model to follow, and the presence of negative character traits as noted by the adolescents themselves. Discussion and Conclusions. Given that the problem of sleep disorders is multifactorial and that war represents a powerful social factor significantly increasing the risk of sleep disorders and contributing to psychological and psychosomatic problems, parents must develop a responsible attitude toward their children’s sleep hygiene. In case of sleep disorders, timely consultation with clinical psychologists and family physicians is recommended to normalize sleep, including identifying underlying causes and planning an optimal daily routine. Taking into account the identified factors associated with the risk of sleep disorders in adolescents living under military conflict conditions will help improve the effectiveness of psychoprophylactic, corrective, and rehabilitation measures aimed at preserving adolescent mental health.